Global Demographic Change and Its Implications for Military Power - Libicki, Martin C.; Shatz, Howard J.; Taylor, Julie E. (RAND Corporation, 2023)
What is the impact of demographics on the prospective production of military power and the causes of war? This monograph analyzes this issue by projecting working-age populations through 2050; assessing the influence of demographics on manpower, national income and expenditures, and human capital; and examining how changes in these factors may affect the ability of states to carry out military missions.